Plant defense mechanism in combined stresses - cellular and molecular perspective - Rafique, Suphia; Quadri, Syed Naved; Abdin, M. Z. (Journal of Plant Stress Physiology, 2024)
The various abiotic stresses negatively influence the growth and development of plants. However, recent predictions of global climate change models have amplified the chances that plants will encounter new and more combinations of abiotic and biotic stresses. The plants adopt different strategies in combined stresses as compared to a single stress. This stress combination can be antagonist or synergistic depending on the interaction of stresses. Plants are sessile, to resists these stresses they activate defense mechanism which are complex cellular and molecular responses under combined stress conditions. At the cellular level, various kinds of biomolecules are produced that have positive and negative effects against stresses. The basic cellular process generates more reactive oxygen species (ROS) in stress conditions and causes extensive damage and inhibition of photosynthesis. Various plant hormones are involved in cellular activations to adapt the plants under stressful conditions. Further, to overcome the adverse effects of stress, the plant activates several molecular cascade mechanisms involving kinases, transcription factors, micro-RNAs, heat shock proteins, epigenetic changes. Besides, plants developed a robust signal perception and transduction mechanism to cope effectively with unfavorable conditions. Phytohormone plays a crucial role in signaling that is activated in response to combined stress conditions and in individual stress which are activated in response to abiotic and biotic stress combinations. Besides, ROS is also involved in signaling. They control a broad range of biological processes and have a conserved signaling network. Therefore, the crosstalk between different signaling pathways activates defense mechanisms and helps in the survival of plants from the various combined abiotic and biotic stress conditions.